2019
DOI: 10.1111/faf.12377
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on lakes by salmon, trout and charr (Oncorhynchus,SalmoandSalvelinus): An evaluation of spawning habitats, rearing strategies and trophic polymorphisms

Abstract: Salmonid fishes may reside within or migrate between stream and lake habitats, or undergo anadromous migrations between freshwater and the ocean. While the degree of anadromy of salmonids has been thoroughly compared, no analogous review has examined the degree of lake use. To assess the extent of reliance on lake habitat in this family, we considered 16 species of salmon, trout and charr from the genera Oncorhynchus, Salmo and Salvelinus, comparing their (a) use of lakes as spawning habitat, (b) rearing strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 245 publications
(373 reference statements)
2
38
1
Order By: Relevance
“…The results of the study suggested a natal homing capability of this species; the Poyang Lake, Yangtze River, and Yellow Sea seemed to be the natal lake, migration pathway, and feeding ground, respectively, for this species [ 48 ]. As indicated by Arostegui and Quinn [ 65 ], based on studies of salmonid fish of the North American, Asian, European, and African ranges, lakes provide spawning, rearing, and refuge habitats and support life-history variants, reproductive ecotypes, and trophic morphs. Unfortunately, anadromous C. nasus individuals have not been found recently in the lakes of Dongting, Gucheng, Taihu, or Dongping.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study suggested a natal homing capability of this species; the Poyang Lake, Yangtze River, and Yellow Sea seemed to be the natal lake, migration pathway, and feeding ground, respectively, for this species [ 48 ]. As indicated by Arostegui and Quinn [ 65 ], based on studies of salmonid fish of the North American, Asian, European, and African ranges, lakes provide spawning, rearing, and refuge habitats and support life-history variants, reproductive ecotypes, and trophic morphs. Unfortunately, anadromous C. nasus individuals have not been found recently in the lakes of Dongting, Gucheng, Taihu, or Dongping.…”
Section: Resultsmentioning
confidence: 99%
“…If so, the actual proportion of strayers among the trout tagged during this study may exceed the proportion reported here. Finally, although brown trout primarily spawn in fluvial habitats, they are capable of successfully spawning in lakes if suitable hydrological conditions are present (Arostegui & Quinn, ). It is possible that some of the mature‐sized lake‐tagged trout that were not detected in either the inflow or outflow were in fact lacustrine spawners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Galaxias maculatus (known as puye in Chile and inanga in New Zealand) is a facultative migrant and is classified as amphidromous, catadromous, potamodromous, and non-migratory (Alò et al, 2019;Górski et al, 2018;Ruiz-Jarabo et al, 2016). Similarly, many salmonids are partial migrants having both migratory and resident forms (e.g., Oncorhynchus mykiss; Baerwald et al, 2016;Ferguson et al, 2019;Hecht et al, 2012), but are often defined as anadromous regardless of the presence of any connection to a marine setting (Arostegui & Quinn, 2019). Partial migration is a rather common phenomenon among fishes.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%